Kompetensi Pengembangan Kewirausahaan Program Pos Pemberdayaan Keluarga (Posdaya Pasir Mulya Kecamatan Bogor Barat Kota Bogor - Atria Widyana; Richard W.E Lumintang (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2013)
Unit family empowerment (Posdaya) is a locus for developing the welfare of families in increasing their income so that people can improve the quality of life. One of the forms in increasing their income by developing entrepreneurship. The activities of its members through Posdaya supported to detail useful skills and knowledge to develop their entrepreneurial endeavors. The purpose of this research is to recoquize the characteristics of the RW 02 as a member of the Posdaya Bina Sejahtera. In addition, analyses the development of entrepreneurship as well as the competencies contained in the activities Village of Posdaya Bina SejahteraBogor Subdistrict Neighborhoods West Pasir MulyaPasir Mulya. The research was carried out by quantitative and qualitative methods using questionnaires and in-depth interview. This research result indicates in the members of posdaya more women in category, productive the end of the age the majority last finished elementary school education and have a job entrepreneurship. The development of entrepreneurship in Posdaya Bina Sejahtera done with through training and assistance. The training and assistance produce competence the development of entrepreneurship in terms of knowledge and skills in the life of a day.Keywords: Posdaya, entrepreneurship, competence